AUDIENCE RECEPTION ON YOUTUBE VIDEO ABOUT CHILDFREE - Kevina Ukraina, Vadhillah; Hasfi, Nurul; Lukmantoro, Triyono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The childfree phenomenon in Indonesia, although still considered taboo, is increasingly being discussed, especially on social media. Data from the Central Statistics Agency shows a 2.1% decline in the marriage rate, which was 1.74 million marriages, to 1.7 million in 2022. In addition, the birth rate has also experienced a significant decline of 30.64% in the last three decades. This decline is thought to be due to various social, economic, and cultural factors, including changes in views on the family and the role of women. The childfree phenomenon has sparked heated debate over traditional values that place children as an essential part of the family and women's identity. This study examines how audiences respond to the childfree narrative in the YouTube video